Pentingnya Budaya Organisasi Kerja Dalam Meningkatkan Produktivitas Kerja - Joben, Joben (CV. Pusdikra Mitra Jaya, 2024)
The aim of this research is to analyze the importance of work organizational culture in increasing work productivity. This research examines various concepts of the importance of work organizational culture in increasing work productivity by assessing through a systematic literature review and identifying research gaps. The method employed in this research is the literature study method. The data collection technique used is literature study obtained from journals and books. Data analysis was conducted using descriptive analysis. The results of the research indicate that if organizational culture is good, employee work productivity will be good, and vice versa. Thus, a good organizational culture will increase employee work productivity. An organizational culture created by good management will encourage better employee work productivity. If employee work productivity always increases significantly over time, then the organization will easily achieve the goals it has set.